Achieving SDG 10: What role for Competition Law and Policy? - Rampai, Karabo (University of the Witwatersrand, Johannesburg, 2024)
nequality has been one of South Africa’s biggest challenges and with stagnating economic growth, the future does not look enticing. If the country wants to ultimately achieve sustainable equality, an extensive legislative scheme that caters for the present and the future is crucial. The implementation of these legislative schemes should not give complete precedence to measures which lead to economic growth. This is because economic growth does not automatically lead to poverty reduction or reduced inequality. Poverty and inequality have increased in most countries over the last decades despite decent economic growth rates because the capital growth mostly goes to the top of the income distribution and does not trickle down. Rather, legislative schemes must apply measures which promote and emphasise participation of historically disadvantaged persons in the economy. This kind of approach is good because it decreases levels of inequality in such a manner that is good for sustainable economic growth. Furthermore, this approach shares similarities with the United Nations Sustainable Development Goal 10: Reducing Inequalities and it is also cognisant of the economic circumstances in South Africa and has had relative success when executed correctly.
A research report submitted in fulfillment of the requirements for the Master of Laws, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Competition Law; Inequality; BBBEE; UN Sustainable Goals; Goal 10; Economic Developmen; SDG-10: Reduced inequalities